Nerve regeneration using a Bio 3D conduit derived from umbilical cord-Derived mesenchymal stem cells in a rat sciatic nerve defect model. - Terunobu Iwai; Ryosuke Ikeguchi; Tomoki Aoyama; Takashi Noguchi; Koichi Yoshimoto; Daichi Sakamoto; Kazuaki Fujita; Yudai Miyazaki; Shizuka Akieda; Tokiko Nagamura-Inoue; Fumitaka Nagamura; Koichi Nakayama; et al. (PLoS ONE)
Human umbilical cord-derived mesenchymal stromal cells (UC-MSCs), which can be prepared in advance and are presumed to be advantageous for nerve regeneration, have potential as a cell source for Bio 3D conduits. The purpose of this study was to evaluate the nerve regeneration ability of Bio 3D conduits made from UC-MSCs using a rat sciatic nerve defect model. Methods A Bio 3D conduit was fabricated using a Bio 3D printer by placing UC-MSC spheroids into thin needles according to predesigned 3D data. The conduit was transplanted to bridge the 5-mm gaps of Lewis rat sciatic nerve, and nerve regeneration was evaluated at 8 weeks (Bio 3D group). Transplantation of autologous nerve segments (autograft) and silicone tubes represented the positive and negative control groups, respectively. In a second experiment, immunological reactions were evaluated in Bio 3D, autograft, and allograft groups by histochemical staining of transplanted segments in Brown Norway rats. Results The mean angle of attack value in the kinematic analysis was significantly better in the Bio 3D group (‒20.1 ± 0.5°) than in the silicone group (‒33.7 ± 1.5°) 8 weeks after surgery. The average diameters of myelinated axons were significantly larger in the Bio 3D group (3.61 ± 0.15 μm) than in the silicone group (3.07 ± 0.12 μm), and the number of myelinated axons was significantly higher in the Bio 3D group (11,201 ± 980) than in the silicone group (8117 ± 646). Histological findings (hematoxylin and eosin [HE] staining and anti-CD3 fluorescent immunostaining) showed that rejection was suppressed in the Bio 3D group compared to the allograft group. Based on macroscopic findings and histological findings (anti-human mitochondrial fluorescent immunostaining), UC-MSCs in the Bio 3D conduit disappeared gradually from week 1 to week 8. Conclusions The Bio 3D conduit prepared from UC-MSCs was superior to the silicone tube and achieved comparable nerve regeneration to the autologous (autograft) group. Rejection was suppressed in the Bio 3D group compared to the allograft group. Although this study used a xenograft model, we speculate that rejection was low due to the characteristics of UC-MSCs. UC-MSCs are a useful cell source for Bio 3D conduits.